2021
DOI: 10.4081/aiua.2021.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Does transition from standard to Retzius-sparing technique in robot-assisted radical prostatectomy affect the functional and oncological outcomes?

Abstract: Objective: To appraise the outcomes on the Retzius-sparing robot-assisted radical prostatectomy (Rs-RARP) learning curve of a surgeon with previous experience of anterior (standard) RARP. Materials and methods: The first 50 cases during the Rs-RARP learning curve (group 1) and 50 cases after the second 100 cases with the standard approach (group 2) were comprised in the study. Patients who used zero or one safety pads were considered continent. Erectile function recuperation was characterized as the competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Of all patients who underwent salvage radiotherapy, 4/21 (19%) patients in the RS-RARP group and 8/21 (38%) patients in the SA-RARP group had a combination of ISUP 4-5 + pT3 + R1 disease ( p = 0.17). Median follow-up in the SA-RARP and RS-RARP groups was 24.5 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] vs. 22 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] months, respectively ( p = 0.008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all patients who underwent salvage radiotherapy, 4/21 (19%) patients in the RS-RARP group and 8/21 (38%) patients in the SA-RARP group had a combination of ISUP 4-5 + pT3 + R1 disease ( p = 0.17). Median follow-up in the SA-RARP and RS-RARP groups was 24.5 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] vs. 22 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] months, respectively ( p = 0.008).…”
Section: Resultsmentioning
confidence: 99%
“…Anil et al [ 34 ] reported on an analysis of data from a cohort of 50 RS-RARP and 50 SA-RARP patients and retrospectively assessed the safety of the switch from an anterior to a posterior approach. They did not report a significant difference in erectile function recovery, early urinary continence recovery, continence recovery at 1 year postoperatively or positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 24 studies comparing RS-RARP to other approaches have been published up to April 15, 2023. Most reports aimed to demonstrate differences between RS-RARP and other approaches in terms of early and late urinary continence (Table 1) [5–8,9 ▪ ,10,11 ▪ ,12–16,17 ▪ ,18,19 ▪ ,20–22,23 ▪ ,24 ▪▪ ,25–28], but none focused on erectile function as primary endpoint. A minority of the studies reported data on sexual function, never finding significant differences among the RARP approaches.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Figure 16). 9,14,[18][19][20]22,23,25 Of the studies included, six reported data about biochemical recurrence (BCR) after a 1-year follow-up. 9,12,16,19,20,24 All of them defined BCR as PSA value ≥ 0.2 ng/mL in two consecutive measures.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…The meta-analysis reported no statistically significant intergroup difference (SMD = -0.14; 95% CI = [−0.41 to 0.12]; Figure 20). [9][10][11][12]14,15,[17][18][19][20][21][22]24 3.6 | Length of stay (LOS)…”
Section: Operation Timementioning
confidence: 99%